2015
DOI: 10.2215/cjn.05630614
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Assessment in Patients Receiving Continuous RRT

Abstract: The effect of AKI and modern continuous RRT (CRRT) methods on drug disposition (pharmacokinetics) and response has been poorly studied. Pharmaceutical manufacturers have little incentive to perform pharmacokinetic studies in patients undergoing CRRT because such studies are neither recommended in existing US Food and Drug Administration (FDA) guidance documents nor required for new drug approval. Action is urgently needed to address the knowledge deficit. The Kidney Health Initiative has assembled a work group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…We showed that CRRT waste (effluent) can serve as a biomatrix for estimating plasma free drug concentrations in lieu of repeated phlebotomy and that interindividual variability in b-lactam pharmacokinetics (PK) undermines target attainment in critically ill patients receiving CRRT (11,12,14). Indeed, recent publications from the Kidney Disease Improving Global Outcomes and the Kidney Health Initiative groups highlight the knowledge gap and need for improved drug dosing in acute renal disease (15,16). It is now clear that one size fits all dosing using standard adjustments to account for renal failure and dialysis does not guarantee adequate plasma concentrations in all or even most patients.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that CRRT waste (effluent) can serve as a biomatrix for estimating plasma free drug concentrations in lieu of repeated phlebotomy and that interindividual variability in b-lactam pharmacokinetics (PK) undermines target attainment in critically ill patients receiving CRRT (11,12,14). Indeed, recent publications from the Kidney Disease Improving Global Outcomes and the Kidney Health Initiative groups highlight the knowledge gap and need for improved drug dosing in acute renal disease (15,16). It is now clear that one size fits all dosing using standard adjustments to account for renal failure and dialysis does not guarantee adequate plasma concentrations in all or even most patients.…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies declined in both NCE groups. Several recent reviews have focused on enrollment inclusion and exclusion criteria for CKD and dialysis patients, as well as the number of subjects who should comprise each renal function category …”
Section: Discussionmentioning
confidence: 99%
“…Indeed only 1 NCE, voriconazole oral, was evaluated to determine PK changes associated with the delivery of CRRT during the 12‐year observation period . The KDIGO consensus group and others have called on regulatory agencies to mandate PK evaluations in AKI patients including those receiving CRRT therapy …”
Section: Discussionmentioning
confidence: 99%
“…The lack of reliable clinical data to guide antibiotic use and the associated risk of under-dosing during CRRT have been identified as major problems—dosing continues to be done largely on an empiric basis [45] (Table 1). Over the next decade, multiple clinical trials evaluating the antibiotics most commonly prescribed to CRRT patients will be performed.…”
Section: Renal Support In 2027: Addressing Crrt’s Current Limitationsmentioning
confidence: 99%